Comparison of Entities in Excerpts from the Novel Perahu Kertas and Its Translation Paper Boats - Nasution, Dea Yuanita; Ningsih, Harni Kartika (Universitas Negeri Semarang, 2023)
A text is a product of the cognitive representation of its producer, including literary and translation texts. To identify the influence of this cognitive background, this research aims to explore shifts in the field of experience in the translation of novels by identifying participants constructing the field. The study utilizes a qualitative method with the IDEATION framework from Systemic Functional Linguistics, specifically taxonomic relations theory. A parallel corpus is used, extracted from excerpts of the Indonesian novel